Cardiac surgery in the afternoon is not associated with increased operative morbidity and mortality. Issue 10 (7th August 2021) - Bianco, Valentino; Aranda‐Michel, Edgar; Serna‐Gallegos, Derek; Kilic, Arman; Kaczarowski, David J.; Dunn‐Lewis, Courtenay; Thoma, Floyd; Navid, Forozan; Sultan, Ibrahim
Abstract: Background: Time of day for surgical procedures has been a topic of considerable controversy, with some suggesting that later operating times are associated with worse outcomes. Methods: All patients who underwent open cardiac surgery from 2011 to 2018 were included. Patients that had ventricular assist devices, heart transplant, transcatheter aortic valves, aortic dissections, and emergent operations were excluded. Primary outcomes included postoperative mortality and survival; secondary outcomes included postoperative complications and readmission. Results: The initial patient population consisted of 7883 patients who underwent index cardiac surgery. Following propensity matching (3:1), there were 2569 patients in the a.m. cohort (7–11 a.m.) and 860 patients in the p.m. cohort (3–11 p.m.). All baseline characteristics were matched to equivalent proportions. Total intensive care unit time following surgery was longer for the a.m. cohort (46.5 vs. 40.0 h; p <.001). Otherwise, there was no significant difference between cohorts including operative mortality (1.83% vs 2.21%; p = .48). On multivariable analysis, p.m. surgery was not significantly associated with 30 days mortality (hazard ratio [HR]: 0.96 [0.60, 1.53]; p = .86] or mortality over the study follow‐up (HR: 0.87 [0.73, 1.03]; p = .10]. For propensity‐matched cohorts, Kaplan–Meier survival at 30 days (97.9% vs. 97.4%; p = .44), 1 (93.4% vs 93.9%; p = .51), and 5 years (80.9% vs. 80.2%; p = .84) was not significantly different between cohorts. Conclusion: Short‐ and long‐term mortality, hospital readmission, and postoperative complications were not significantly different between patients that underwent cardiac surgery starting in the a.m. versus patients who had cases that started in the afternoon.